The English Instructor’s Perception of Private Tutoring for Secondary School Students in Indonesia - Musa, Nur Ainun; Wulandari, Sami'an; Ramdani, Amaliah; Reskyani, Reskyani; Noni, Nurdin (Tamaddun Life, 2024)
Many families utilize English private tutoring to help their children with their homework or improve their skills; in doing so, they are taking part in an additional "shadow education" system on top of regular schooling. This research utilized qualitative methods to explore the perspectives of English instructors on private tutoring for secondary school students. Two English instructors were interviewed to obtain their views on private tutoring. The interview technique involved creating an interview guide and using structured online interviews. The data was categorized into core themes or categories, with both participants enthusiastically expressing their perspectives on the causes and impacts of English private tutoring. The result showed that private tutoring is perceived as beneficial for students struggling with English lessons, as it allows them extra time outside school hours and enhances their understanding. Instructors must provide personalized knowledge and engage students in innovative sessions. Parents play a crucial role in guiding students' activities. Private tutoring can boost students' intention to learn English and increase their learning behavior. Instructors tailor their approach to meet the needs of private students